2020
DOI: 10.7224/1537-2073.2019-032
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and Impact of a Clinical Pharmacist in a Hospital-Based Neurology Clinic Treating Patients with Multiple Sclerosis

Abstract: Background: Clinical pharmacists are uniquely positioned to assist with the complexities of medication management for patients with multiple sclerosis (MS). The objective of this study is to describe clinical pharmacy services provided as well as provider satisfaction and perceived impact of incorporating a clinical pharmacist in MS patient care. Methods: This study was conducted in two parts: a retrospective chart review and provider survey conducted in an outpatient neurology clinic at an acad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Sub-specialties such as epilepsy and multiple sclerosis may also leverage and benefit from telepharmacy services. [ 13 , 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…Sub-specialties such as epilepsy and multiple sclerosis may also leverage and benefit from telepharmacy services. [ 13 , 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…There is a limited number of studies that speci cally evaluate the impact of a clinical pharmacist in an MS clinic. Most recently, in a retrospective chart review, May et al found that 55% of a neurology clinical pharmacists interventions were medication access related in the Grady Health System neurology clinic in Atlanta and found high satisfaction among providers with clinical pharmacist involvement [7]. Therefore, the objective of the study is to evaluate the impact of a clinical pharmacist in interdisciplinary MG and MS clinics.…”
Section: Introductionmentioning
confidence: 99%